Development and examination of the technology of steel deoxidation at outlet from blast furnace using results of measuring of oxygen activity in metal - D. S. Jakshuk; E. V. Ivanov; S. V. Terletsky; V. V. Enders (Литьë и металлургия)
There is examined and developed the technology of deoxidation of steel by aluminium with using measuring of oxygen activity in metal before outlet from chipboard by means of oxygen sensors ''CELOX"' of the firm "ELECTRO-NITE*.